Comparison of Intertidal Invertebrate Assemblages at Four Sites around Rottnest Island, Western Australia After Seven Years of Marine Heatwaves. - Husen Rifai; Bayu Perisha; Firman Zulpikar; Jeverson Renyaan; Milani Anggiani; Asep Rasyidin (Journal Omni-Akuatika, 2020)
A study aiming to compare the abundance and species composition of invertebrates among four sites (Strickland East, Strickland West, Strickland Far East and North Point) on intertidal rocky platforms around Rottnest Island, Western Australia was conducted in January 2018. Eight quadrats with 1m by 1m dimension were haphazardly placed at each of three zones in the sampling site including the inner, middle and outer zone in relation to the shoreline in order to obtain the data of invertebrate community structure. The result of a one-way ANOVA test with a robust covariance matrix showed that the intertidal invertebrate abundance among the four sampling sites was statistically significant different (P<0.05). Then, a further test using Tukey post hoc analysis found that invertebrate abundance at Strickland East was significantly different with the assemblage of invertebrate at North Point, Strickland West and Strickland Far East at the level of significance of 1%, 5% and 10%, respectively. Whereas the cluster analysis revealed that there were two clusters of invertebrate species at Rottnest Island. In the future, it is recommended to conduct an invertebrate community structure monitoring program consistently every year covering all intertidal sites around Rottnest Island in order to obtain reliable data useful for conservation and management purposes.